IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DALAM ORGANISASI - Prabowo, Budi; Acep; Wijaya; Nadya; El; Nabila (IndOmera, 2024)
The concept of human resource management (HR) emerged in the mid-1980s. The overall goal of HRM is to improve human resources so that success can be achieved in the organization. The HRM system can be a benchmark for an organization's ability to develop and obtain new opportunities. This research was conducted using qualitative research. collect, analyze, and compile sources organization from articles, books, reports, and other research. The research approach used will help provide an overview of Human Resource Management and help analyze problems in Human Resource Management. Where the role is to organize, manage based on the vision and mission so that the organization's goals can be achieved optimally. The main goal of human resource management is to ensure access to a ready workforce for an organization. HRM functions to meet the basic needs of management and staff. The importance of HR in a company to achieve organizational goals. Human Resources and Human Resource Management have a very important role in the success of a company by focusing on managing, developing and empowering human resources to achieve organizational goals. Related theories help in understanding and implementing best practices in human resource management in the work environment.